Analisis Minat Keikutsertaan Siswa dalam Bimbingan Belajar dan Implikasinya pada Hasil Belajar Biologi di SMA - Umam, Syaiful Ishlahul; Alimah, Siti; Yuniastuti, Ari (FMIPA UNNES, 2017)
Interest determines the yield. Higher learning interests can improve learning outcomes. This study aims to analyze the interest of students in participate the guidance of learning and its implications on the results of biology learning in SMAN 1 Semarang. The methodology research uses mixmethod with sequential exploration strategy. The research was conducted in the field using four methods, namely observation, interview, documentation, and questionnaire. Data were obtained in the form of description of student interest and student interest score. Furthermore, compared with the final exam results of students. Data were analyzed by correlation, regression and t-test which then explained. The results showed that 70% of students interested to participate the guidance of learning and based on linear regression analysis there is a contribution of student interest on the results of biological studies with r2 = 0.87 (Î± = 0.003). Pearson product moment correlation analysis obtained coefficient value 0.295 with significance 0.003 indicates that there is a positive relationship between interest with biology learning result. Based on the independent test ttest shows tvalue = 5.12 â‰¥ ttable = 2.32 (Î± = 0.00; n = 100). Based on the results of research and discussion can be concluded that some students are interested in participate the guidance of biology learning. Students' interest in learning outcomes has a positive relationship with low criteria and influences biological learning outcomes. There are differences in biology learning outcomes of students who participate the guidance of learning and not participate in tutoring.